2017
DOI: 10.1016/j.devcel.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Cell Invasion In Vivo via Rapid Exocytosis of a Transient Lysosome-Derived Membrane Domain

Abstract: Summary Invasive cells use small invadopodia to breach basement membrane (BM), a dense matrix that encases tissues. Following the breach, a large protrusion forms to clear a path for tissue entry by poorly understood mechanisms. Using RNAi screening for defects in C. elegans anchor cell (AC) invasion, we found that UNC-6(netrin)/UNC-40(DCC) signaling at the BM breach site directs exocytosis of lysosomes using the exocyst and SNARE SNAP-29 to form a large protrusion that invades vulval tissue. Live-cell imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 74 publications
2
102
0
Order By: Relevance
“…Active vesicle trafficking and cytoskeleton dynamics required for BM invasion are thought to be energy intensive (Altieri, 2017;Cunniff et al, 2016;Naegeli et al, 2017). We thus wanted to examine how mitochondria regulate BM invasion in MMPÀ animals, where there may be a greater energy requirement to breach the non-proteolyzed BM.…”
Section: Localized Mitochondria and Atp Production Facilitatesmentioning
confidence: 99%
“…Active vesicle trafficking and cytoskeleton dynamics required for BM invasion are thought to be energy intensive (Altieri, 2017;Cunniff et al, 2016;Naegeli et al, 2017). We thus wanted to examine how mitochondria regulate BM invasion in MMPÀ animals, where there may be a greater energy requirement to breach the non-proteolyzed BM.…”
Section: Localized Mitochondria and Atp Production Facilitatesmentioning
confidence: 99%
“…At that time, it was thought that only modified lysosomes (also referred to as “lysosome‐related organelles”) present in specialised secretory cells such as cytotoxic lymphocytes had the required molecular machinery to undergo Ca 2+ ‐regulated exocytosis (Griffiths, ). Subsequent studies revealed that Ca 2+ ‐dependent fusion of lysosomes with the plasma membrane is a widespread process (Kukic, Kelleher, & Kiselyov, ; Li, Ropert, Koulakoff, Giaume, & Oheim, ; Luzio, Pryor, & Bright, ; Miao, Li, Zhang, Xu, & Abraham, ; Naegeli et al, ; Samie et al, ; Settembre, Fraldi, Medina, & Ballabio, ; Wang & Yamada, ) regulated by specific membrane‐associated proteins such as SNAREs, the exocyst complex (Naegeli et al, ), the ubiquitously expressed synaptotagmin VII Ca 2+ sensor, and the lysosomal Ca 2+ channel mucolipin‐1 (TRPML1; Martinez et al, ; Rao, Huynh, Proux‐Gillardeaux, Galli, & Andrews, ; Samie et al, ). Interestingly, studies using total internal fluorescence microscopy in Chinese hamster ovary cells and in mouse embryonic fibroblasts showed that the large majority of lysosomes undergoing exocytosis in response to Ca 2+ belongs to a pre‐existing peripheral population of lysosomes (Jaiswal, Andrews, & Simon, ).…”
Section: A Surprising Discovery: Conventional Lysosomes Behave As Ca2mentioning
confidence: 99%
“…The usual interpretation of such a result would be that Dg is involved in the targeting of ECM secretion upstream of Rab10 rather than in ECM assembly in the extracellular space. In C. elegans, Dg acts as a diffusion barrier to define a precise subcellular domain for ECM remodeling (Naegeli et al, 2017). One could imagine that the DAPC has a similar function in follicle cells, by defining the position where the Rab10 secretory route is targeted.…”
Section: The Dapc Acts As An Organizer Of the Basal Domain Of Epithelmentioning
confidence: 99%
“…This complex is expressed in a large variety of tissues and is implicated in many congenital degenerative disorders. Loss of function studies in model organisms have revealed an important morphogenetic role for Dg during development, usually linked to defects in ECM secretion, assembly or remodeling (Clements et al, 2017;Henry and Campbell, 1998;Satz et al, 2010;Bello et al, 2008;Buisson et al, 2014;Naegeli et al, 2017;Yatsenko and Shcherbata, 2014).…”
Section: Introductionmentioning
confidence: 99%